PERENCANAAN PEMBANGUNA DESA MELALUI PARTISIPASI MASYARAKAT DI DESA SEMANGUT UTARA KECAMATAN BUNUT HULU KABUPATEN KAPUAS HULU - Muhammad Efendi E.42009035 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
Thisthesisis intendedtodetermine the extent ofpublic participation in theplanningof developmentinthe village ofNorthSemangut Utara with a focus onresults Musrembang Desa in manufacturingplanning Dokumen Rencana Pembangunan Jangka Menengah Desa (RPJMDes) andalsoatroubledbuildingsassociatedpublic participation. The titlewas liftedbythe results ofthe earlyobservationsresearchersconsidered thatthe level ofcommunity participationin development planningis stilllow.Selectthe location ofthis studyin Desa Semangut Utara Kacamatan Bunut Hulu Kabupaten Kapuas Hulu. Subjects wereruralNorthSemangut Utara associatedwiththeirparticipationin the planningandconstruction ofvillage governmentand Badan Pemberdayaan Desa, Perempuan dan Kelaurga Berencana empowerment ofvillage officialsandrelatedagencies andorganizationsin the villageSemangut Utara. The conclusionof this researchis thepublic awareness of theimportance oftheirparticipationin development planningis stilllow.  To the researcherstry to explain thetheoryput forward byAnggelabout thereare several factors thataffecta person's inclinationtoparticipate, namely age, gender, education, occupationandincome, and length ofstay. Withthe exposuretheoryis expected togivegoodfeedbackto the Governmentas well asVillageSemangutUtara and Badan Pemberdayaan Desa, Perempuan dan Keluarga Berencana Kabupaten Kapuas Hulu so thatplanningcan bedone well.Keywords: Planning, Development, CommunityParticipation